Reconstructing Loss Accounting through Islamic Spirituality and Local Cultural Values: An Islamic Ethnomethodology Study - Thalib, Mohamad Anwar; Bau, Nadia Saputri R.; Surdana, Rizky Rizhaldy (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2025)
Purpose: This study investigates why Islamic boarding schools (pesantren) in Gorontalo conceptualize and manage losses not merely as financial deficits but as cultural and spiritual concerns. It addresses the gap in accounting research that rarely examines loss accounting through the lens of local wisdom and Islamic values. Methodology: This research employs a qualitative method using a spiritual paradigm and an Islamic ethnomethodology approach. Data were collected through in-depth interviews, observations, and documentation, and analyzed using five interpretive stages: charity, knowledge, faith, revealed information, and excellence. Findings: The study identifies four concrete strategies used by pesantren to avoid or reduce losses: maximizing school fee collection with community involvement, intensively socializing institutional programs, securing external funding sources, and framing the management of losses as a form of worship. These practices reflect the Gorontalo cultural value Eya dila pito-pito’o (“God does not close His eyes”), which strengthens accountability and institutional resilience. Novelty: The research offers a culturally grounded model of loss accounting that integrates local wisdom and Islamic spirituality. This contributes a new conceptual lens for understanding financial practices in faith-based educational institutions and enriches the accounting literature on pesantren.